ASSOCIATION BETWEEN THE DEGREE OF DIABETIC RETINOPATHY AND DIABETIC MACULAR EDEMA - Andhika Guna Dharma; Maharani Maharani; Riski Prihatningtias; Muhamad Taufik Mahar; Henry Setiawan; Ayu Anggraini Kusumaningrum; Arief Wildan (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
INTRODUCTION: WHO estimates more than 150 million diabetes patients worldwide. One of the complications of diabetes is diabetic retinopathy which is recognized as the leading cause of blindness in the working-age population and the cause of 12% of new cases of blindness each year due to macular edema, vitreous hemorrhage, and tractional retinal detachment. Macular edema is the most common cause of decreased visual acuity. The relationship between macular edema and the degree of retinopathy is unclear, so further research is needed. This study aimed to analyze the incidence of macular edema with the degree of diabetic retinopathy.METHOD: This study used a cross-sectional method. Samples were taken from the Retina Data Register at the National Diponegoro Hospital Eye Polyclinic of all diabetic retinopathy patients who attended National Diponegoro Hospital from July to December 2020 who were recruited as participants. The variables measured included the incidence of macular edema and the degree of diabetic retinopathy. Measurements using fundoscopy, slit lamp and condensing lens + 78D according to ETDRS (Early Treatment Diabetic Retinopathy Study) criteria by an ophthalmologist. Data analysis used a bivariate difference test for 2 groups. The statistical test used was the Kruskal-Wallis test, which was significant if p ≤ 0.05.RESULTS: In this study, out of 150 eyes examined, 28 (18.7%) had macular edema. 4 (2.7%) eyes were diagnosed with Moderate NPDR, 3 (2%) eyes were diagnosed with Severe NPDR. In eyes diagnosed with PDR with or without VH or TRD, 21 (14%) eyes had macular edema. The p-value was 0.03 with the Kruskal-Wallis test, where p ≤ 0.05.CONCLUSION: There is a significant difference between the degree of diabetic retinopathy and the incidence of macular edema. The incidence of macular edema is higher in the more severe degrees of diabetic retinopathy.